2010
DOI: 10.3109/08923971003725144
|View full text |Cite
|
Sign up to set email alerts
|

In vivoandin vitroanti-inflammatory effects of a novel derivative of icariin

Abstract: Icariin is the major active constituent of Epimedii Herba. Our recent study showed that icariin displayed anti-inflammatory potential. One novel derivate of icariin is 3,5,7-Trihydroxy-4'-methoxy-8-(3-hydroxy-3-methylbutyl)-flavone (ICT). Little is known about ICT's pharmacological activities. In our study, the anti-inflammatory properties of ICT were evaluated. Murine RAW264.7 cells and C57BL/6J mice stimulated by lipopolysaccharide (LPS) was used as in vitro and in vivo inflammatory model, respectively. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
3
24
0
1
Order By: Relevance
“…Similarly, a dose-dependent impairment of TNF-α production was observed in PBMC and human primary monocytes. Our previous MTT assay has verified that the anti-inflammatory effects of ICT did not depend on the cytotoxity [22]. In this study, no significant cell death was observed after the cells were treated with ICT at various concentrations (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Similarly, a dose-dependent impairment of TNF-α production was observed in PBMC and human primary monocytes. Our previous MTT assay has verified that the anti-inflammatory effects of ICT did not depend on the cytotoxity [22]. In this study, no significant cell death was observed after the cells were treated with ICT at various concentrations (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies demonstrated that icariin could be used to treat septic arthritis and brain dysfunction induced by LPS [27,28]. In our previous study, we demonstrated that ICT, a novel flavonoid derivative of icariin, had similar effects to icariin in murine macrophages [22]. In the current study, we demonstrate that ICT blocks the ability of THP-1 monocytic cell line to produce TNF-α in response to LPS stimulation.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The above formula is frequently used in treatment of chronic inflammatory diseases in the respiratory system and immunocompromised diseases in TCM. Increasing evidence revealed that QRHX and its components, extracts, and derivative have the ability of anticancer and anti-inflammation [1214]. Nevertheless, there are no reports which concerned the alleviated effects of QRHX on macrophage-mediated lung cancer.…”
Section: Introductionmentioning
confidence: 99%